Silicon facilitated the physical barrier and adsorption of cadmium of iron plaque by changing the biochemical composition to reduce cadmium absorption of rice roots - Saihua Liu; Xionghui Ji; Zhiliang Chen; Yunhe Xie; Shengying Ji; Xin Wang; Shufang Pan (Ecotoxicology and Environmental Safety, 2023)
Silicon effectively inhibits cadmium (Cd) uptake in rice, iron plaque on root surface was the primary link and first interface of Cd entering into rice root. To elucidate the mechanism of iron plaque under silicon treatment on root Cd uptake, the morphological characteristics of iron plaque, mechanisms of Cd adsorption of iron plaque and effect of iron plaque on Cd uptake by rice roots of Yuzhenxiang (YZX) and Xiangwanxian (XWX) rice varieties were studied by employing energy spectrum analysis technique, non-invasive micro-test technique, and isothermal-kinetic adsorption method. Scanning electron microscopy-X-ray energy dispersive (SEM-EDX) analysis showed that denser crystal structure of iron plaque was observed at Si treatment, silicon promoted the thickening of iron plaque and strengthened the isolation of iron plaque to Cd, which reduced the Cd content of white roots of YZX and XWX varieties by 30.2% and 20.9% respectively. However, the blocking effect of iron plaque on Cd was weakened under silicon treatment with iron plaque removed, Cd content in iron plaque of YZX and XWX cultivars was significantly decreased by 36.3% and 18.4%, Cd concentrations in white root and shoot was significantly increased, and the influxes of Cd2+ at elongation and maturation zone of root were increased in multiples. The results of adsorption test showed that the adsorption process of iron plaque was mainly a monolayer adsorption completed by boundary diffusion. The X-ray photoelectron spectroscopy (XPS) results demonstrated that silicon changed the biochemical composition of iron plaque and increased the density of the carbon-oxygen bound groups on iron plaque, which is the most likely reasons for the higher affinity of Cd adsorption ability of iron plaque observed in the silicon treated iron plaque. This study suggested the silicon-facilitated iron plaque have played critical effects in controlling the Cd accumulation in rice roots by changing the morphology and chemical composition of iron plaque.